2020
DOI: 10.1111/bjh.17286
|View full text |Cite
|
Sign up to set email alerts
|

TKI dose reduction can effectively maintain major molecular remission in patients with chronic myeloid leukaemia

Abstract: Targeted therapy for chronic myeloid leukaemia (CML) has allowed for a near-normal patient life-expectancy; however, quality of life and aggravation of existing co-morbidities have posed new treatment challenges. In clinical practice, TKI dose reduction occurs frequently, often on multiple occasions, because of intolerance. We conducted a retrospective 'real-world practice' review of 246 patients receiving lower than standard dose (LD) TKI after the achievement of major molecular response (MR3), because of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Interestingly, of the 94 patients in MMR, 54.2% achieved a molecular response level of MR4.0 or higher with a lowered dose. 76 patients discontinued TKI after 1.76 years of low dose treatment, and the 2-year TFR rate in these patients was 74.1% (61). Consistent with the DESTINY trial, a TKI step-down strategy before treatment discontinuation may be a promising strategy to improve TFR.…”
Section: De-escalation Tki Dose -An Alternative Strategymentioning
confidence: 65%
“…Interestingly, of the 94 patients in MMR, 54.2% achieved a molecular response level of MR4.0 or higher with a lowered dose. 76 patients discontinued TKI after 1.76 years of low dose treatment, and the 2-year TFR rate in these patients was 74.1% (61). Consistent with the DESTINY trial, a TKI step-down strategy before treatment discontinuation may be a promising strategy to improve TFR.…”
Section: De-escalation Tki Dose -An Alternative Strategymentioning
confidence: 65%
“…The survival rate of patients with CML has significantly improved, and an increasing number of patients pursue a dose‐optimization strategy to improve quality of life. In clinical practice, TKI dose reduction is an important strategy for reducing severe adverse reactions or to improve patient adherence 25,26 . A mathematical model suggested that a TKI dose reduction of at least 50% would not affect long‐term clinical outcomes 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, TKI dose reduction is an important strategy for reducing severe adverse reactions or to improve patient adherence. 25,26 A mathematical model suggested that a TKI dose reduction of at least 50% would not affect long-term clinical outcomes. 27 Our results suggested that imatinib trough concentrations >1000 ng/ml in most patients administered 300 mg imatinib daily, which indicated that dose reduction to 300 mg daily could achieve MMR, from the perspective of imatinib concentration.…”
Section: Discussionmentioning
confidence: 99%
“…9 97.4% (37/38) of patients remained in MMR with 50 mg dasatinib or lower, consistent with another study that reported a 3-year MRFS in MMR of 94.5%. 10 Importantly, of nine patients not in MMR, six (66.7%) achieved MMR or deeper molecular response with low dasatinib dose treatment. In our study, all patients (n=10) on half-dose nilotinib experienced maintenance of MMR.…”
Section: A B C Dmentioning
confidence: 96%